2016
DOI: 10.3390/ma9010016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Polyacrylamide Solution Used for Remediation of Petroleum Contaminated Soils

Abstract: Biopolymers are viewed as effective and eco-friendly agents in soil modification. This study focuses on the wettability analysis of polyacrylamide (PAM) solutions for soil remediation. The contact angle, surface tension, and viscosity of PAM solutions were experimentally evaluated in air- and decane-biopolymer solution systems. Furthermore, a micromodel was used to investigate the pore-scale displacement phenomena during the injection of the PAM solution in decane and or air saturated pores. The contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 44 publications
3
17
0
1
Order By: Relevance
“…Compared with other biopolymers in the literature review, the viscosity in this study (1.523 × 10 −3~1 .867 × 10 −3 Pa·s) is higher, at the same concentration (2 g/L) and shear rates (1~10 s −1 ), than chitosan (7.76 × 10 −4~2 .415 × 10 −3 Pa·s) but is lower than the viscosities of Xanthan gum (0.0665~0.168 Pa·s) and polyacrylic acid (PAA) (0.126~0.408 Pa·s) [8]; (2) the viscosity increases with an increase in the biopolymer solution concentration, within the range of 0-10 g/L ( Figure 7); (3) the viscosity decreases with increased shear rates, from 1 s −1 to 10 s −1 (Figure 8), which is consistent with the previous study [7]. presented that the viscosities of the biopolymer solutions decrease with an increase in the shear rate between 3.4 s −1 and 17 s −1 [7]. At a given biopolymer concentration (0-10 g/L) and shear rate (1-10 s −1 ), the viscosity change of PEO and SA by the increased concentration of PEO (or SA) is more prominent than the viscosity change of PEO and SA by the decreased shear rate.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Compared with other biopolymers in the literature review, the viscosity in this study (1.523 × 10 −3~1 .867 × 10 −3 Pa·s) is higher, at the same concentration (2 g/L) and shear rates (1~10 s −1 ), than chitosan (7.76 × 10 −4~2 .415 × 10 −3 Pa·s) but is lower than the viscosities of Xanthan gum (0.0665~0.168 Pa·s) and polyacrylic acid (PAA) (0.126~0.408 Pa·s) [8]; (2) the viscosity increases with an increase in the biopolymer solution concentration, within the range of 0-10 g/L ( Figure 7); (3) the viscosity decreases with increased shear rates, from 1 s −1 to 10 s −1 (Figure 8), which is consistent with the previous study [7]. presented that the viscosities of the biopolymer solutions decrease with an increase in the shear rate between 3.4 s −1 and 17 s −1 [7]. At a given biopolymer concentration (0-10 g/L) and shear rate (1-10 s −1 ), the viscosity change of PEO and SA by the increased concentration of PEO (or SA) is more prominent than the viscosity change of PEO and SA by the decreased shear rate.…”
Section: Resultssupporting
confidence: 80%
“…Thus they do not influence geo-environments after their use. Recently the characteristics of water-soluble polymers, including contact angle, interfacial tension, and viscosity, have been explored for the better utilisation of biopolymers in soil remediation and EOR [7,8]. Cao et al (2016) presented the characteristics of biopolymers, such as chitosan, PEO, xanthan gum, SA, and polyacrylic acid, in order to use them for soil remediation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoshoots of micromodels where PAM solution was displaced against air and decane were taken. The still images and videos captured were analysed using Image J software for computation of biopolymer saturation and PAM-Decane displacement ratios, Jung et al (2016). It was observed that the flow rate effect is more prominent for decane.…”
Section: Characterization Of Polyacrylamide (Pam) Solution By Jung Etmentioning
confidence: 99%
“…It seems proven that the physic-chemical properties in the slurry can be modified in wet grinding due to changes in physical and chemical conditions (such as size distribution, concentration of solids, temperature, shear rate, pH value, the use of grinding aids, etc.). The use of polyacrylamide (PAM) in water as a viscosity modifier has been broadly studied previously [17,18].…”
Section: Introductionmentioning
confidence: 99%